Teaching for better thinking : the classroom communityof inquiry - Sharp, Ann Margaret. (Australian Council for Educational Research, 1995)
THis book is about: The dynamics of the inquiring community; The making of meaning; Thinking philosophy and philosophy for children; The practice of philosophy in the classroom; Ethical inquiry in the classroom; ...